Granville Bantock (1868-1946) : a guide to research - Dressler, John Clay, 1949- (Clemson University Press, 2020)
"Granville Bantock: A Guide to Research provides both researchers and British music aficionados an entry to documents, books, articles, recordings, and the like currently available for further study about Bantock's life and music. Location and descriptive details of the manuscripts that are extant will assist those looking to construct editions of especially those works which have remained in manuscript and updated editions of those works which were initially published nearly 100 years ago. A discography provides insight into the wide variety of recording companies that first served Bantock's music. Included in the book are sections about: academic theses and dissertations, citations of locations of many of Bantock's letters, and an index that cross-references all of these details to the works which they highlight is a major help to the reader"--